Feeding the Nation for a Better Future: Preserving Peace through an Agricultural Cooperation between Indonesia and China - Abdullah, Adiyat; Nurika, Rizki Rahmadini (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2019)
This paper explores the potential of cooperation between Indonesia and China in agricultural sector, considering that they are having similar problem in agriculture, which is limited land for farming while they have to feed their great number of people. To analyze this concern, the concept of multi-track diplomacy will be used. It views the process of international peacemaking as a living system. The result shows that through the multi-track diplomacy, the peacemaking process will be conducted by state and non-state actors in a scattered-activities frame, then peace will spill over from the government to the society and vice versa.